A Cognitive Tool for Ethical Decision Making: A Case for ACED IT. Issue 3 (3rd April 2017) - Stenmark, Cheryl K.; Kreitler, Crystal M.
Abstract : The present study examined two forms of a cognitive tool (ACED IT map), which is designed to facilitate ethical decision making, along with expressive writing. Results demonstrated that participants completing the original ACED IT were more likely to identify (a) more steps to implementing a solution, (b) more barriers to solution implementation, and (c) more solutions to those barriers than participants who completed the modified ACED IT, those who engaged in expressive writing, and those in the control group. These findings suggest that cognitive tools such as ACED IT may be of considerable value for individuals who are presented with ethical dilemmas.